Perjuangan Kapten Samadikun dalam Pertempuran Laut Cirebon Tahun 1947 - Shavirin Rahmat Tullah Saputro; Siti Fauziyah; Angga Pusaka Hidayat (Publikasi Berkala Pendidikan Ilmu Sosial, 2025)
This paper aims to elaborate on the role of Captain Samadikun in the battle to defend Indonesia's independence as part of the conflict between Indonesia and the Netherlands, reflecting post-independence tensions. Samadikun was involved in the Battle of the Cirebon Sea on January 5, 1947. The battle occurred because the Dutch considered the Cirebon naval squadron (ALRI Cirebon), led by Samadikun, to have breached the blockade. This was seen as a violation of the status quo established through the Linggajati Agreement. The research method employed is the historical method, encompassing heuristics, criticism, interpretation, and historiography. The results show that post-independence, Indonesia fought to gain sovereignty, both through diplomacy and military means. Samadikun was also involved in building the naval fleet in Cirebon. Ultimately, Samadikun sacrificed his life defending the Cirebon sea area. Despite facing the superior weaponry of the Dutch, the ALRI under Samadikun’s command made significant efforts to defend the waters of Cirebon. The resistance of the ALRI led to the sinking of the KRI Gajah Mada and the death of the ship's commander, Samadikun, along with other personnel. Samadikun's sacrifice reflects the efforts to defend Indonesia's independence during the early stages of the revolution.